1999
DOI: 10.1084/jem.189.9.1507
|View full text |Cite
|
Sign up to set email alerts
|

Humoral and Cell-mediated Autoimmune Reactions to Human Acidic Ribosomal P2 Protein in Individuals Sensitized to Aspergillus fumigatus P2 Protein

Abstract: A panel of cDNAs encoding allergenic proteins was isolated from an Aspergillus fumigatus cDNA library displayed on the surface of filamentous phage. Solid phase–immobilized serum immunoglobulin E (IgE) from A. fumigatus–allergic individuals was used to enrich phage displaying IgE-binding molecules. One of the cDNAs encoded a 11.1-kD protein that was identified as acidic ribosomal phosphoprotein type 2 (P2 protein). The allergen, formally termed rAsp f 8, shares >62% sequence identity and >84% sequence homology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
109
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(111 citation statements)
references
References 31 publications
1
109
0
Order By: Relevance
“…Cross-reactivity between allergens and closely related homologous human Ags is often observed in allergic individuals suffering from chronic atopic diseases (8 -11) and potentially contribute to exacerbation and/or perpetuation of chronic allergic reactions (6,10). These studies provide strong evidence for in vitro and in vivo humoral and cell-mediated IgE autoreactivity in patients suffering from long-lasting atopic diseases (8,11). Structural studies have shown that the availability of the crystal structure of a given allergen and its human homolog allows a detailed definition of the residues potentially involved in cross-reactivity (12).…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…Cross-reactivity between allergens and closely related homologous human Ags is often observed in allergic individuals suffering from chronic atopic diseases (8 -11) and potentially contribute to exacerbation and/or perpetuation of chronic allergic reactions (6,10). These studies provide strong evidence for in vitro and in vivo humoral and cell-mediated IgE autoreactivity in patients suffering from long-lasting atopic diseases (8,11). Structural studies have shown that the availability of the crystal structure of a given allergen and its human homolog allows a detailed definition of the residues potentially involved in cross-reactivity (12).…”
mentioning
confidence: 76%
“…Perhaps the most interesting class of pan-allergens includes environmental allergens sharing structural homology to self-Ags. These structures, including manganese superoxide dismutase, acidic ribosomal P 2 proteins, cyclophilins, and profilins (9,11,12,20,38), have been implicated in exacerbation and/or perpetuation of severe atopic disorders. In contrast to allergenicity, which is an intrinsic property of many different molecular structures, Ab-mediated cross-reactivity among homologous proteins is largely determined by common structural features shared between protein families (13).…”
Section: Discussionmentioning
confidence: 99%
“…However, whether Th2 cells or some regulatory cells, known to mediate some forms of nasal tolerance (67), mediate the effects of Asp f 2 in IPA remains to be determined. The occurrence of autoreactivity in patients suffering from chronic A. fumigatus allergy (39,40) indicates the complexity of the allergic responses to Aspergillus. A number of studies indicate that lung DC play a primary role in surveillance of pathogenic Ags and initiation of a primary immune response in the lung (47,68,69).…”
Section: Discussionmentioning
confidence: 99%
“…This class most likely induces symptoms through molecular mimicry between shared B-and T-cell epitopes present in homologous pairs of molecules (110)(111)(112). Based on the solved crystal structures of the environmental allergens MnSOD, cyclophilin and thioredoxin, reactivity to self-antigens showing sequence homology with environmental allergens can be clearly traced back to conserved amino acid residues clustered on the surface of the IgE-binding molecules.…”
Section: Mechanisms: Inflammatory Mechanismsmentioning
confidence: 99%